Healthier cassava: wealthier farmers? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The National Agricultural Research Organisation (NARO) of Uganda has developed a cassava variety that is resistant to the Ugandan variant of cassava mosaic disease. The disease broke out in 1988 in the Luwero district in northern Uganda and rapidly...